EMPIRICAL STUDY OF THE PROBABILITY OF DEFAULT IN CASE OF ROMANIAN COMPANIES LISTED ON STOCK EXCHANGE - Marton Noemi, Racz Timea Erzsebet; Furdek Balazs - Marton; Farkas Dalma - Zsuzsa; Petru Tunde Petra (Annals of the University of Oradea: Economic Science, 2011)
The importance of estimation of a firm's probability of default increased significantly during the economic and financial crisis for financial institutions, which can be explained by the fact that the share of nonperforming loans increased in this period. The probability of default can be estimated with structural models, which have on base the methodology developed by Merton (1974), methodology used by Moody's Corporation (known as KMV Merton model). The aim of this study is to estimate the probability of default of companies listed on Bucharest Stock Exchange using this methodology. This approach was widely used in the literature by many researchers (i.e., Kealhofer and Kurbat (2000), Crosbie and Bohn (2002), Duffie and Wang (2004), Bharath and Shumway (2004, 2008)). In Romania this methodology was empirically tested by Codirlaşu (2007), who estimated using Merton's methodology the probability of default of companies listed on the Bucharest Stock Exchange, respectively by Bobircă et al. (2008), where the probabilities of default were estimated in case of 42 companies listed on the Bucharest Stock Exchange for 2000-2008 time period. In this paper we used Merton's model, which assumes that a company defaults if the value of its assets is less than the promised dept repayment at time T. The process of estimating the probability of default starts from the following firm specific variables: the market value of the firm's assets, the share prices, the value of the liabilities and the risk-free rate. The analyzed period is 2003-2010, containing the economic and financial crisis period, too. Analyzing the financial statements of the companies listed on the Bucharest Stock Exchange, we determined the input parameters of the model and calculated the quarterly probabilities of default of each analyzed company. According to our results the probabilities of default have a reduced value in the majority of the cases.